2017
DOI: 10.1007/s00066-016-1095-4
|View full text |Cite
|
Sign up to set email alerts
|

DART-bid for loco-regionally advanced NSCLC

Abstract: BackgroundTo report acute and late toxicity with long-term follow-up, and to describe our experiences with pulmonary dose constraints.MethodsBetween 2002 and 2009, 150 patients with 155 histologically/cytologically proven non-small cell lung cancer (NSCLC; tumor stages II, IIIA, IIIB in 6, 55 and 39%, respectively) received the following median doses: primary tumors 79.2 Gy (range 72.0–90.0 Gy), lymph node metastases 59.4 Gy (54.0–73.8 Gy), nodes electively 45 Gy; with fractional doses of 1.8 Gy twice daily (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Organs at risk (OAR), such as the esophagus, central vessels and airways, spinal cord, lungs, and heart were routinely contoured, and dose volume histograms of both initial and re-irradiation plans were used to determine the cumulative radiation exposure of each critical organ. On the basis of a previous evaluation of long-term toxicity after a single course of high-dose chemo-radiation, which revealed that a dose maximum of 80 Gy to the esophagus was associated with a 33.5% clinically relevant grade 2 or 3 toxicity, the D max was set at 100 Gy [12,16]. Okamoto et al showed in a small cohort of long-term survivors that a D max of 110 Gy to trachea and main bronchi can be well tolerated, and therefore we adopted the same constraints [17].…”
Section: Radiation Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Organs at risk (OAR), such as the esophagus, central vessels and airways, spinal cord, lungs, and heart were routinely contoured, and dose volume histograms of both initial and re-irradiation plans were used to determine the cumulative radiation exposure of each critical organ. On the basis of a previous evaluation of long-term toxicity after a single course of high-dose chemo-radiation, which revealed that a dose maximum of 80 Gy to the esophagus was associated with a 33.5% clinically relevant grade 2 or 3 toxicity, the D max was set at 100 Gy [12,16]. Okamoto et al showed in a small cohort of long-term survivors that a D max of 110 Gy to trachea and main bronchi can be well tolerated, and therefore we adopted the same constraints [17].…”
Section: Radiation Therapymentioning
confidence: 99%
“…The maximum volume that could receive more than the above-specified cumulative dose was set at 1 mL. As for the lungs, a V20 total lung < 50% was used on the basis of a previous publication by our group [16]. Regarding cardiac toxicity, QUANTEC suggests dose constraint of V25 heart < 10%, which is associated with a risk of 1% cardiac mortality in 15 years [19].…”
Section: Radiation Therapymentioning
confidence: 99%
“…Accordingly, lung toxicity remains a crucial dose limiting factor, and dose escalation trials with conventionally fractionated radiotherapy have been limited by severe lung toxicity [ 25 27 ]. Due to the development of novel radiotherapy techniques, including intensity modulated radiotherapy (IMRT) [ 5 , 6 ] and volumetric modulated arc therapy (VMAT) [ 20 ], and radiation qualities, such as and proton therapy [ 28 ], radiation exposure of normal lung tissue can be significantly reduced.…”
Section: Introductionmentioning
confidence: 99%